2024
DOI: 10.1021/acs.langmuir.3c02817
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of the Fluorination Effect on the Penetration of Nanoparticles across Lipid Bilayers

Min Wang,
Song-Di Ni,
Yue-Wen Yin
et al.

Abstract: The fluorinated decorations have recently been widely used in many biomedical applications. However, the potential mechanism of the fluorination effect on the cellular delivery of nanoparticles (NPs) still remains elusive. In this work, we systemically explore the penetration of a perfluoro-octanethiol-coated gold NP (PF-Au NP) and, for comparison, an octanethiol-coated gold NP (OT-Au NP) across lipid bilayers. We also investigated the effect of these two types of NPs on the properties of lipid bilayers. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Acetonitrile was modeled using a flexible six-site potential model introduced by Kowsari and Tohidifar . The LJ parameters for BnBr, TBA + , and I – were taken from the literature. The van der Waals interactions of the solute with Au (111) were represented by Lennard-Jones potential described by Heinz et al Several studies have demonstrated that these parameters can qualitatively replicate interactions between the metal surface and the solution interface, , while the Lennard-Jones parameters for interactions in solution effectively capture physical phenomena in the bulk.…”
Section: Methodsmentioning
confidence: 99%
“…Acetonitrile was modeled using a flexible six-site potential model introduced by Kowsari and Tohidifar . The LJ parameters for BnBr, TBA + , and I – were taken from the literature. The van der Waals interactions of the solute with Au (111) were represented by Lennard-Jones potential described by Heinz et al Several studies have demonstrated that these parameters can qualitatively replicate interactions between the metal surface and the solution interface, , while the Lennard-Jones parameters for interactions in solution effectively capture physical phenomena in the bulk.…”
Section: Methodsmentioning
confidence: 99%